Application of Cutting Stock Problem in Minimizing The Waste of Al-Quran Cover - Noor Saif Muhammad Mussafi (Kaunia: Integration and Interconnection Islam and Science, 2016)
Cutting stock problem is the problem of cutting standard-sized pieces of stock material, such as vinyl rolls (synthetic leather) into pieces of specified sizes while minimizing material wasted. The study of cutting stock problem is expected to provide an alternative solution to publishing industrial. This study examines the cutting stock problem based on illustrative example of Quran Publisher using the integer programming. The problem is transformed into optimization model so that it can be solved using solver menu in Microsoft Excel. The results provide decision that meets the consumer demand and has a minimum waste of raw material that used for Al-Quran cover.